2021
DOI: 10.3390/pharmaceutics13081305
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Evaluation of the In Vitro Permeation Parameters of Topical Products with Non-Steroidal Anti-Inflammatory Drugs through Strat-M® Membrane

Abstract: Pharmaceutical products containing non-steroidal anti-inflammatory drugs (NSAIDs) are among the most prescribed topical formulations used for analgesic and antirheumatic properties. These drugs must overcome the skin barrier to cause a therapeutic effect. Human skin has been widely used as a model to study in vitro drug diffusion and permeation, however, it suffers from many limitations. Therefore, to perform in vitro permeation test (IVPT), we used a Strat-M® membrane with diffusion characteristics well-corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…We already have some information about permeation across the Strat-M membrane correlating well with that through human skin [14,15,21] as well as animal skin [27]. In addition, the Strat-M membrane has low batch-to-batch variability, is easy to use, and does not need special storage conditions [28]. In our study, we demonstrated that the permeation profile across the Strat-M membrane was similar to HSE (Table 2), but the general permeation data (Q and J) were significantly higher (p < 0.05) (Figure 3) in the case of the Strat-M membrane.…”
Section: Discussionmentioning
confidence: 87%
“…We already have some information about permeation across the Strat-M membrane correlating well with that through human skin [14,15,21] as well as animal skin [27]. In addition, the Strat-M membrane has low batch-to-batch variability, is easy to use, and does not need special storage conditions [28]. In our study, we demonstrated that the permeation profile across the Strat-M membrane was similar to HSE (Table 2), but the general permeation data (Q and J) were significantly higher (p < 0.05) (Figure 3) in the case of the Strat-M membrane.…”
Section: Discussionmentioning
confidence: 87%
“…For poorly water-soluble drugs, adding solubilizers such as Tween-80, ethanol, and isopropanol in the release medium is recommended [ 57 , 58 , 59 ]. PBS containing 20% isopropanol at pH 7.4 was chosen as the receptor media in both the drug-release and drug-permeation studies to achieve the required sink conditions.…”
Section: Resultsmentioning
confidence: 99%
“…PBS containing 20% isopropanol at pH 7.4 was chosen as the receptor media in both the drug-release and drug-permeation studies to achieve the required sink conditions. This was because sink conditions are attained when the equilibrium solubility of drugs in the dissolving medium is at least three times the volume required for drug saturation [ 59 ]. In addition, these tests were carried out using PBS solution containing 20% isopropanol (pH 7.4) at 37 ± 0.5 °C and 600 rpm to simulate physiological conditions, as has been previously described in [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the work presented by Tiwari et al (2020), the non-ionic EAs such as TW80 could contribute to deformation of the transfersomes, thereby played a main role in improving the drug permeation [ 44 ]. Moreover, the concentration of the drug and the physicochemical characteristics of the formulation can also significantly affect the drug permeation [ 45 , 46 ]. The significantly higher penetration efficiency exhibited by AATGs compared to hydroethanolic AA in gel could be due to the constituents of transfersomes and this proves the requirement of a carrier base delivery system for AA dermal delivery.…”
Section: Resultsmentioning
confidence: 99%